2014
DOI: 10.13175/swjpcc179-13
|View full text |Cite
|
Sign up to set email alerts
|

Elevated tumor markers in coccidiomyocosis of the female genital tract

Abstract: The female genital tract is rarely involved by coccidioidomycosis. We describe a woman with disseminated coccidioidomycosis involving the female pelvic organs associated with elevated tumor markers CA 125 and CA 19-9. She had no fevers and the initial clinical suspicion was a malignancy because of the elevated tumor markers. At exploratory laparotomy a total abdominal hysterectomy and bilateral salpingooophorectomy were performed because of the suspicion of a malignancy. Subsequent pathology demonstrated cocci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Remarkably, the CA-125 level was high. Previous studies have demonstrated increased CA-125 levels in granulomatous diseases including pelvic coccidiomycosis and tuberculosis [22]. In one study, 40% of active pulmonary TB patients had a raised serum CA-125 with a mean level of 38.9 U/mL.…”
Section: Discussionmentioning
confidence: 96%
“…Remarkably, the CA-125 level was high. Previous studies have demonstrated increased CA-125 levels in granulomatous diseases including pelvic coccidiomycosis and tuberculosis [22]. In one study, 40% of active pulmonary TB patients had a raised serum CA-125 with a mean level of 38.9 U/mL.…”
Section: Discussionmentioning
confidence: 96%
“…In our case, the peritoneal plaques were initially suspected to represent peritoneal carcinomatosis. In two previously published cases, female genital coccidioidomycosis mimicked ovarian cancer due to the presence of an ovarian mass in combination with elevated levels of the tumor-markers CA125 and CA 19–9 [ 12 , 13 ] and malignant-appearing nodules on all serosal surfaces of the peritoneum [ 13 ]. Pregnancy is a known major risk factor for disseminated disease.…”
Section: Discussionmentioning
confidence: 99%